Hydrophobic effects in a simple Diels-Alder reaction in water - Sarma, D.; Pawar, S. S.; Deshpande, Suvarna S.; Kumar, Anil (Tetrahedron Letters, 2006)
The endolexo ratio for a simple Diels-Alder reaction carried out in water has been used to argue that hydrophobic effects can dominate the geometries of the transition states. (c) 2006 Elsevier Ltd. All rights reserved.